Romanistisches Jahrbuch (De Gruyter, 1948)
Romanistisches Jahrbuch (RJb) presents essays and reviews on current research topics regarding one or several Romance languages, with a particular focus on Ibero-Romance Studies. It is the only academic journal that regularly informs about the representation of Romance Linguistics, Literary and Cultural Studies at German and Austrian universities.